É que Glauber acha feio o que não é espelho: a invenção do Cinema Brasileiro Moderno e a configuração do debate sobre o ser cinema nacional. - Lima, Frederico Osanan Amorim (2012)
The main objective of this work consisted in establishing a wide interlocution among the several subjects involved with the sense productions about the Brazilian Cinema, taking the notion of modern as the reference for discussion. The analyses of texts and books produced by moviemakers and movie critics allowed the vision of articulated aspects which sustain the Modern Brazilian Cinema and it also allowed the problematization of the production places considering a specific speech and the implications produced by its institution as a regime of true. In order to confront the predominant explicative model in the historiography of Brazilian Cinema, movies and texts about the movie experimentalism highlighting the ones produced in the 1970s in the city of Teresina (PI) were used. This genre allowed, according to our point of view, the establishment of a new reading possibility of the Brazilian Culture of the 1960s and 1970s. Considering the conceptual aspect, this work aimed the benefits proposed by the post-structuralistic analyses of scholars as Michel Foucault, Hayden White, Keith Jenkins, among others.